PHOTODISSOCIATION DYNAMICS OF TERT-BUTYL NITRITE (S-2) AND TERT-BUTYL HYDROPEROXIDE AT 248-250 NM - August, J; Brouard, M; Docker, M; Milne, C; Simons, J; Lavi, R; Rosenwaks, S; Schwartzlavi, D (1988)
The technique of Doppler-resolved laser-induced fluorescence spectroscopy has been employed to study the scalar and vector properties of fragments generated via photodissociation of two large polyatomic molecules, tert-butyl nitrite excited into its S2 state at 250 nm and tert-butyl hydroperoxide photolyzed at 248 nm into its first absorption continuum. Experiments on the former system confirm the planar nature of the dissociation, which generates NO fragments with vNO ⊥ JNO, and the A′ symmetry of the parent molecular S2 state. For tert-butyl hydroperoxide, the energy disposal in the OH fragments is similar to that found for H2O2 photolyzed at 248 nm, but both β, the OH fragment translational anisotropy, and β00(22), the (vOH,JOH) correlation, are significantly smaller than for H2O2. These differences (and others) in the photofragment vector properties are discussed in terms of changes in the kinematics and the potential energy surfaces for the two systems. In particular the low translational anisotropy found in tert-butyl hydroperoxide can be explained in terms of angle bending, leading to "slingshot" photodissociation dynamics. © 1988 American Chemical Society.